Language and Conflict: Arguing for Interdisciplinarity and Usefulness - Janicki, Karol (Bergen Language and Linguistics Studies, 2017)
This paper consists of two parts. Part 1 concerns the benefits of interdisciplinary research, and it concludes with a philosophical section in which the question is raised of what kinds of linguistic research can be seen as socially valid. In Part 2, I discuss my own recent research, which I consider socially relevant. It includes two major topics: (1) language and conflict, and (2) folk linguistics. Under the heading of ‘language and conflict’, I have investigated some of the ways language can contribute to both instigating and alleviating conflict. In my opinion, the way we view meaning, communication, and definitions is central to our understanding of and avoiding language-ridden conflict. As for ‘folk linguistics’, which concerns the layperson’s views of language, I have investigated the question of what the lay people see as the most important language-related problems. The paper concludes with a statement supporting research in the field of the humanities.